2018
DOI: 10.1200/jgo.2016.008748
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Beliefs as Potential Targets for Breast Cancer Awareness Efforts to Decrease Late-Stage Presentation in Uganda

Abstract: PurposeTo assess breast cancer beliefs in Uganda and determine whether these beliefs are associated with factors potentially related to nonparticipation in early detection.MethodsA survey with open- and close-ended items was conducted in a community sample of Ugandan women to assess their beliefs about breast cancer. Linear regression was used to ascertain associations between breast cancer beliefs and demographic factors potentially associated with early detection, including socioeconomic factors, health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…VHTs and dispensary staff should be educated to recognize the signs and symptoms of breast cancer, to know the appropriate level of care for patient referral (currently level 5 or 6 until capacity is built at lower levels of the health system), and to deliver culturally appropriate health messages regarding breast cancer awareness to women 13‐16 . These efforts can be integrated into established systems; for example, prior research demonstrated the success of educational strategies in Uganda for improving outcomes for the management of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…VHTs and dispensary staff should be educated to recognize the signs and symptoms of breast cancer, to know the appropriate level of care for patient referral (currently level 5 or 6 until capacity is built at lower levels of the health system), and to deliver culturally appropriate health messages regarding breast cancer awareness to women 13‐16 . These efforts can be integrated into established systems; for example, prior research demonstrated the success of educational strategies in Uganda for improving outcomes for the management of infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, while many women believed that early detection would result in a cure, most believed by the time they self-detected symptoms it was too late. [14] These results, obtained in women without breast cancer, suggested multiple modifiable factors that could affect women’s participation in breast cancer detection practices. Simultaneously, these results seem to contradict the multiple barriers, not modifiable in the near term (socially determined barriers), Ugandan breast cancer survivors and others provided in prior studies (e.g., economic, social support) as possible reasons most women delay diagnosis or do not successfully complete the path to diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…A study on prostate cancer in Uganda [ 12 ] found that only 10.3% of respondents had good knowledge of the symptoms. Low awareness, negative beliefs, and myths (eg, belief that cancer is caused by witchcraft) have also been reported for breast [ 13 ] and cervical cancer [ 14 ] in Uganda, contributing to low screening rates (4.8% to 30%) and late presentation (over 80% of patients presenting with advanced disease) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%